Transformasi Peran Orang Tua dan Guru Menghadapi Krisis Perkembangan Bahasa Anak Usia Dini di Era Digital - Desi Herlianti; Moh. Ari Wibowo; Heni Adhianata (Lembaga Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Keguruan dan Ilmu Pendidikan PGRI Sampang, Indonesia, 2026)
Early childhood language development is a crucial aspect of preparing children for the next stage of their education. Parental satisfaction regarding a child's language development is influenced not only by the quality of instruction provided at school but also by the role parents play in providing language stimulation at home. This study aims to analyze the factors influencing parental satisfaction levels regarding children's language development at Tut Wuri Handayani Kindergarten in Sampang. The research focuses on two independent variables—quality of language instruction (X1) and the parental role in language stimulation at home (X2)—and one dependent variable: parental satisfaction with the child's language development (Y). A quantitative descriptive method was employed, with data collected via questionnaires distributed to 30 parents acting as respondents. The research instrument underwent validity and reliability testing, and the data were analyzed using descriptive statistics, specifically by calculating the mean score for each variable indicator. The results indicate that, overall, the level of parental satisfaction regarding children's language development falls into the